Exploring The Implementation Process of an ESP Program for Engineering Students: A CIPP-Based Evaluation - Mimin Aminah; Muchlas Suseno; Samsi Setiadi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study evaluates the implementation of an English for Specific Purposes (ESP) program for engineering students at a private university in West Java, Indonesia, using the Context, Input, Process, and Product (CIPP) evaluation model. The study involved 15 participants, including 10 Mechanical Engineering students, 3 ESP instructors, and 2 program administrators. Employing a qualitative case study approach, data were collected through semi-structured interviews, classroom observations, and document analysis over a four-month period. The findings revealed that the program successfully identified students' professional language needs, particularly in technical writing and oral presentation, aligning well with industry and academic expectations. Quantitative data indicated an average 18% improvement in students' writing and presentation scores over one semester. Despite these gains, listening skills remained underdeveloped due to the limited integration of audio-based materials and listening-focused instruction. The curriculum applied project-based learning and included some authentic materials but was hindered by insufficient instructor training and inadequate resource support. The study underscores the importance of aligning curriculum design, pedagogical strategies, and resource allocation with learner needs. It also affirms the utility of the CIPP model in evaluating ESP programs holistically and provides practical implications for curriculum developers, language educators, and institutional policymakers committed to enhancing the quality and impact of ESP instruction in engineering education.